A Meta-Analysis of Endoscopic vs. Microscopic Transsphenoidal Surgery for Non-functioning and Functioning Pituitary Adenomas: Comparisons of Efficacy and Safety - Guo, Shengfu; Wang, Zidong; Kang, Xiaokui; Xin, Wenqiang; Li, Xin (Frontiers in Neurology, 2021)
Abstract Background: Although microscopic (MTSS) and endoscopic transsphenoidal surgery (ETSS) are effective approaches for treating nonfunctioning (NFPA) and functioning pituitary adenomas (FPA), a consensus is still unidentified whether there are differences in the risk of postoperative complications between the two surgical approaches. Method: A meta-analysis of the study that MTSS versus ETSS for NFPA and FPA was conducted by searching the electronic databases of PubMed Cochrane Library, and EMBASE, from the date of establishment of electronic databases to September 2020 based on PRISMA guidelines. Results: In this study, a total of 15 studies were involved, hailing from Belgium, the USA, India, Finland, France, Korea, China, and Canada. We enrolled 964 patients in the ETSS and 943 patients in the MTSS group. In patients with the NFPA, the ETSS group was related to a higher incidence of post-operative gross-total resection (GTR). (OR = 1.655, 95% CI 1.131 to 2.421, P=0.010). In participants with FPA, the results illustrated that the ETSS group had higher rates of visual improvement (OR=2.461, 95% CI 1.109 to 5.459) and gross-total resection (OR = 2.033, 95% CI 1.335 to 3.096), as well as lower meningitis rates (OR =0.195, 95% CI 0.041 to 1.923). In participants with acromegaly, no significant difference was shown in the postoperative complications. Conclusion: Based on current evidence, participants with NFPA treated by endoscopy were related to the higher rates of GTR; patients with FPA treated by ETSS were related to higher rates of visual improvement and GTR, as well as a lower rate of meningitis.